ハイパー演算子の結合法則

ハイパー演算子の結合法則

(1)

\(n=1,2\)のとき、

\[ a^{\left(n\right)}\left(b^{\left(n\right)}c\right)=\left(a^{\left(n\right)}b\right)^{\left(n\right)}c \]

(2)

\(n=0\)または\(n=3,4,\cdots\)のとき、

\[ a^{\left(n\right)}\left(b^{\left(n\right)}c\right)\ne\left(a^{\left(n\right)}b\right)^{\left(n\right)}c \]

-

\(a^{\left(n\right)}b\)はハイパー演算子

(1)

\begin{align*} a^{\left(1\right)}\left(b^{\left(1\right)}c\right) & =a+b+c\\ & =\left(a^{\left(1\right)}b\right)^{\left(1\right)}c \end{align*}

\begin{align*} a^{\left(2\right)}\left(b^{\left(2\right)}c\right) & =abc\\ & =\left(a^{\left(2\right)}b\right)^{\left(2\right)}c \end{align*}

(2)

\(n=0\)のとき、

\begin{align*} a^{\left(0\right)}\left(b^{\left(0\right)}c\right) & =a^{\left(0\right)}\left(c+1\right)\\ & =c+2 \end{align*}

\begin{align*} \left(a^{\left(0\right)}b\right)^{\left(0\right)}c & =c+1 \end{align*}

となるので、
\[ a^{\left(0\right)}\left(b^{\left(0\right)}c\right)\ne\left(a^{\left(0\right)}b\right)^{\left(0\right)}c \]

\(n=2,3,\cdots\)のとき、

\(c=0\)とする。

\begin{align*} a^{\left(n\right)}\left(b^{\left(n\right)}0\right) & =a^{\left(n\right)}1\\ & =a \end{align*}

\[ \left(a^{\left(n\right)}b\right)^{\left(n\right)}0=1 \]

となり、

\[ a^{\left(n\right)}\left(b^{\left(n\right)}0\right)\ne\left(a^{\left(n\right)}b\right)^{\left(n\right)}0 \]

となるので、一般に

\[ a^{\left(n\right)}\left(b^{\left(n\right)}c\right)\ne\left(a^{\left(n\right)}b\right)^{\left(n\right)}c \]

となる。

ページ情報

タイトル

ハイパー演算子の結合法則

URL

https://www.nomuramath.com/yv2kkqea/

SNSボタン